Improving Students’ Vocabulary Achievement through Anagram - Rina Herawati Barus; Jonris Tampubolon (English Lecturers and Teachers Association (ELTA), 2022)
This study is aimed at improving the students’ vocabulary achievement through anagram. This study was conducted by using classroom action research. The subject of this study was the 2009/2010 ten grade students of SMA Negeri 1 Pancur Batu which consisted of 30 students. For collecting data, the instrument used quantitative data (vocabulary test) and qualitative data (diary notes, interview sheet and observation sheet). Based on the data, it was found that the students’ score increased from the pre test until the post test of the first and the second cycle. In the pre test, the mean of the students was (54,93), in the post test of the first cycle was (68) and the mean of the students of the second cycle was (82,46). The students’ score also increased from pre test to post test cycle I until post test cycle II. It was found that teaching vocabulary through anagram can improve the students’ vocabulary achievement. It is concluded that teaching vocabulary through anagram is significantly effective in teaching vocabulary. Keywords: Classroom Action Research, Vocabulary Achievement, Anagram